Ready for practice: What child and family health nurses say about education. (February 2015) - Fowler, Cathrine; Schmied, Virginia; Psaila, Kim; Kruske, Sue; Rossiter, Chris
Summary Background Australia has a well-established universal child and family health service predominately staffed by specialist/qualified child and family health nurses. Two common and interrelated concerns are the need for nurses to be ready for practice after completing a nursing education program and the means to ensure ongoing nursing competence. Objective To investigate the readiness of CFH nurses to practise after qualification and their continuing engagement with learning. Design The study used an interpretive descriptive approach. Setting This paper presents data from four questions from a larger survey of child and family health nurses across Australia. Participants 1098 child and family health nurses responded to the survey. Method Qualitative survey responses from the four education questions were analysed using inductive thematic content analysis. Results Five significant themes were identified: hands-on experience (student clinical practice/placement); drawing on prior experience; learning on the job; learning (learning over time); and barriers to learning. Conclusion This paper provides insights into nurses' readiness for practice at the completion of a postgraduate child and family health nursing qualification and their maintenance of competence and specialist knowledge. It highlights: the need for clinical placement to be retained and enhanced; the significant contribution of more experienced child and family health nurses mentoring newly graduated child and family health nurses; the need for minimum education standards; the importance of reviewing education courses in relation to graduates' readiness for child and family health nursing practice; the importance of supporting ongoing professional development; and the removal of barriers to accessing education opportunities.